DAIRY MARKET: GLOBAL DEVELOPMENT TRENDS AND UKRAINIAN PROSPECTS - KOZAK, Olga; HRYSCHENKO, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyses the main global milk production development trends, including the largest producing countries, among the 20 of which is Ukraine. The main trends and reasons for changes in milk production, cow number and milk yield, as well as the peculiarities of the dairy farm transformation around the globe and in Ukraine, were revealed. The trend of decreasing the number of dairy farms and increasing the average farm size, characteristic of most countries, including Ukraine, has been shown. At the same time, in developed countries, production concentration occurs much faster than in developing countries. The causes of milk price fluctuations on the world market and their reflection on the Ukrainian market have been determined. It was found that the milk price is currently a record and will remain high until the end of the year - at least 50 USD/100 kg. At the same time, most farmers do not cover the costs of milk production, primarily due to the rising prices of resources (feed, fertilizers, wages, etc.). At that time, the global milk demand is consistently growing and will remain so in the future. A justified need to expand the export of dairy products from Ukraine during and after the war, especially in the context of the trade liberalisation with the European Union, began in May 2022. An assessment of the prospects for the development of the world dairy market until 2030, taking into account modern factors, was carried out influence, among which the war in Ukraine takes a special place. It has been proven that the increase in milk production in Ukraine is beneficial both for the domestic and the world dairy market.
Keywords: milk; dairy products; production; dairy farms; development; world market; prices; international trade; forecast; war